PENGARUH PENERAPAN MODEL PEMBELAJARAN YURISPRUDENSIAL PADA MATA KULIAH HUKUM PIDANA TERHADAP SIKAP ANTI KORUPSI DITINJAU DARI KESADARAN HUKUM MAHASISWA (STUDI PADA PRODI PPKN FKIP UNS) - dkk, Triana Rejekiningsih (PKn Progresif, 2012)
The purpose of this study was to 1) Determine the influence of jurisprudential learning model in the course of the Criminal Law of the student anti-corruption stance Prodi CIVICS FKIP UNS; 2) Knowing the influence of awareness of anti-corruption laws on the attitudes of students Prodi PPKn FKIP UNS; 3) Knowing the interaction effect of jurisprudential learning model the Criminal Law course with legal consciousness of the student anti-corruption stance Prodi PPKn FKIP UNS. In line with the aim of the study, the research method used is descriptive quantitative method, which means pendiskripsian correlational and litigious nature of the data in the form of figures and are present in the population. Populations and samples in this study were students of semester 2 PPKn Guidance and Counseling Program UNS 2009 school year are taking courses in Criminal Law number 60 people. Then the data were analyzed with statistical methods followed by Multiple Linear Regression Analysis, is to look for relationships between variables Y with two or more variables X. The formula y = a + + BX2 bX1. This study concludes: 1) There is a significant influence of jurisprudential application of learning models in the course of criminal laws against anti-corruption stance Prodi PPKn FKIP UNS students. Through the application of jurisprudential learning model anti-corruption stance of students will be increased. This can be seen as through the application of jurisprudential model of student learning can be actively engaged in learning activities, 2) There is a significant effect on anti-corruption stance Prodi PPKn FKIP UNS students in terms of the legal consciousness of students. Legal awareness should translate into attitudes, the more one is able to understand and implement anti-corruption values ??embodied growing anti korups and 3) There is an interaction effect of the application of jurisprudential learning model in the course of criminal law with the legal awareness of anti-corruption stance of students Prodi PPKn FKIP UNS. Through the application of appropriate learning model chosen by the faculty and the high legal awareness by the students will form an anti-corruption stance.